2021
DOI: 10.1101/2021.02.05.429872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osteomacs support osteoclast-mediated resorption and contribute to bone pathology in a postmenopausal osteoporosis mouse model

Abstract: Osteal macrophages (osteomacs) support osteoblast function and promote bone anabolism, but their contribution to osteoporosis has not been explored. While mouse ovariectomy models have been repeatedly used, variation in strain, experimental design and assessment modalities, have contributed to no single model being confirmed as comprehensively replicating the full gamut of osteoporosis pathological manifestations. We validated an ovariectomy model in adult C3H/HeJ mice and demonstrated that it presents with hu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Immune cells interact with osteoblasts and osteoclasts through cell-cell contacts or secretion of exosomes and are closely associated with various inflammatory bone diseases [24]. It has been found that activated macrophages are closely linked to the severity of osteoporosis [25]. Secretion factors are determinants for regulation of macrophages on bone cells, and specific cytokines are released in response to stimulating factors such as LPS, causing cellular damage and oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells interact with osteoblasts and osteoclasts through cell-cell contacts or secretion of exosomes and are closely associated with various inflammatory bone diseases [24]. It has been found that activated macrophages are closely linked to the severity of osteoporosis [25]. Secretion factors are determinants for regulation of macrophages on bone cells, and specific cytokines are released in response to stimulating factors such as LPS, causing cellular damage and oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%